Depth of maximum of air-shower profiles at the Pierre Auger Observatory. I. Measurements at energies above 10(17.8) eV - Aab, A.; Abreu, Pedro; Aglietta, Marco; Ahn, E. J.; Al Samarai, I.; Albuquerque, I. F. M.; Allekotte, I.; Allen, J.; Allison, P.; Almela, A.; Alvarez Castillo, J.; Alvarez-Muniz, Jaime; et al. (Physical Review D, 2014)
We report a study of the distributions of the depth of maximum, X-max, of extensive air-shower profiles with energies above 10(17.8) eV as observed with the fluorescence telescopes of the Pierre Auger Observatory. The analysis method for selecting a data sample with minimal sampling bias is described in detail as well as the experimental cross-checks and systematic uncertainties. Furthermore, we discuss the detector acceptance and the resolution of the X-max measurement and provide parametrizations thereof as a function of energy. The energy dependence of the mean and standard deviation of the X-max distributions are compared to air-shower simulations for different nuclear primaries and interpreted in terms of the mean and variance of the logarithmic mass distribution at the top of the atmosphere.